FAKTOR- FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA SEKTOR PROPERTY, REAL ESTATE, DAN KONSTRUKSI BANGUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA PERIODE 2014-2018 - Aprianto Miduk Pandapotan Saragih Aprianto (Akuntansi Prima, 2020)
This research aims to test and analyze how Profitability (Net Profit Margin), Firm Size, Leverage (Debt To Equity Ratio), and Liquidity (Cash Ratio) affect dividend policies on Property Sector, Real Estate, and Building Construction companies listed on the Indonesia Stock Exchange for the period 2014-2018. This type of research is quantitative research. This research uses the explanatory research properties of this research population of 63 Property and Real Estate Sector companies with Purpose Sampling sampling techniques of 20 Property and Real Estate Sector companies that meet the criteria The results of this study show simultaneously Profitability (Net Profit Margin), Firm Size, Leverage (Debt To Equity Ratio), and Liquidity (Cash Ratio) have a significant and significant effect on the Dividend Policy in trade sector companies, services, and investments listed on the Indonesia Stock Exchange for the period 2014-2018 with Fhitung > Ftabel (9,963 < 2,76) and significant 0,00 ≤ 0,05 received and Ha rejected which means variable Profitability, The size of liquidity and leverage companies simultaneously has a significant impact on property sector, real estate, and building construction companies listed on the Indonesia Stock Exchange for the period 2014 – 2018. This means that 26,6% of the company's value variation can be explained by its three independent variables namely Profitability, Company Size, Liquidity, and Leverage while the remaining73.4%.